Does the Relation Between Humor Styles and Subjective Well-Being Vary Across Culture and Age? A Meta-Analysis - Jiang, Feng; Lu, Su; Jiang, Tonglin; Jia, Heqi (Frontiers in Psychology, 2020)
An earlier review (Schneider et al., 2018) examined the connection between humor styles and mental health. The present article supplements and extends Schneider et al.’s review by surveying a broader concept, subjective well-being (SWB), and investigating the moderating effects of culture and age. To this end, we collected data from 85 studies, with 27,562 participants of varying ages and cultures. Meta-analysis results indicate that affiliative and self-enhancing humor enhances SWB, whereas aggressive and self-defeating humor damages SWB. Culture and age do not moderate the relation between humor styles and SWB. We discuss implications for better understanding of the relationships among culture, age, humor, and SWB.